The importance of the dominant hemisphere in the organization of bimanual movements. - Serrien, D; Cassidy, M; Brown, P (2003)
The successful control of upper limb movements is an essential skill of the human motor system. Yet, the neural organization of bimanual actions remains an issue of debate. Their control can be directed from both hemispheres, or, coordinated motion might be organized from the dominant (left) hemisphere. In order to unravel the neural mechanisms of bimanual behavior, we analyzed the standard task-related and directed coherence between EEG signals picked up over the primary sensorimotor cortices in right-handed subjects during unimanual as well as bimanual in-phase (symmetrical) and anti-phase (asymmetrical) movements. The interhemispheric coherence in the beta frequency band (>13-30 Hz) was increased in both unimanual and bimanual patterns, compared to rest. During unimanual actions, the drive in the beta band from one primary sensorimotor cortex to the other was greater during movement of the contralateral as opposed to ipsilateral hand. In contrast, during bimanual actions, the drive from the dominant to the non-dominant primary sensorimotor cortex prevailed, unless task constraints induced by an external perturbation resulted in a substantial uncoupling of the hand movements, when interhemispheric coherence would also drop. Together, these results suggest that the contralateral hemisphere predominantly organizes unimanual movements, whereas coupled bimanual movements are mainly controlled from the dominant hemisphere. The close association between changes in interhemispheric coupling and behavioral performance indicates that synchronization of neural activity in the beta band is exploited for the control of goal-directed movement.